On the Favard theory without $H$ -classes for differential-functional equations in Banach spaces - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.937 We obtain necessary and sufficient conditions for the existence and uniqueness of solutions bounded on the real axis withprecompact sets of values of linear almost periodic differential-functional equations in Banach spaces.